Stakeholder requirements affecting urban freight transportation to and from construction sites in the city - Landqvist, Maria; Rowland, Anna (My University, 2014)
Due to the great urbanization during the last centuries urban freight transportation has become increasingly important in order to solve the complexities arising when performing construction work in densified cities. When building in urban areas different types of stakeholders express a wide variety of requirements due to the urban freight transportation. A common transformation of modern cities has been coastal areas developing from heavy industrial focus into residential, livable cities. Thereby, urban areas are adapting due to sustainable premises such as in Västra Hamnen in Malmö, Norra Djurgårdsstaden and Hammarby Sjöstad in Stockholm, but also in RegionCity, belonging to the future project Älvstaden in Gothenburg. Hence it is necessary to support the urban development and manage the enhanced population in the cities where accessibility and transport conditions are restricted. Therefore, the purpose of this master’s thesis is to identify stakeholders and their respective requirements related to construction projects in residential areas. When mapping the stakeholders and requirements relating to urban freight transportation to and from the construction site, it might be possible to facilitate logistical transport solutions in the densified city. Thereby, the number of stakeholder requirements appearing too late in the construction process might be minimized. By combining theoretical findings within urban freight transportation and choosing interview respondents belonging to the different categories of academia, governmental as well as business, it was possible to take different objectives and agendas into account. Due to the different interviewee segments, it became clear that each category had different insights and viewpoints. The academia emphasized research relating to for example efficient route planning, the governmental respondents highlighted social benefits enabling livable urban areas for the entire society and the interviewees belonging to the business segment most often had an agenda relating to monetary goals. When identifying the different stakeholders associated to urban freight transportation at the construction site as well as their respective requirements belonging to the three pillars of sustainability, different matrices were established with the help of an analysis model. Thereby, the stakeholders identified as shipper, freight transport operator, customer, authorities as well as additional stakeholders were clearly stated, with most of the actors belonging to the shipper or authority segment. When further segmenting the different stakeholder requirements according to when these appear during the construction process, most of the demands appear during the actual construction process. However, the authorities might state their requirements already during the pre-construction phase, while the customers on the other hand state their requirements during the post-construction-phase.
Keywords: Transport; Hållbar utveckling; Övrig industriell teknik och ekonomi; Transport; Sustainable Development; Other industrial engineering and economics